Analisis Dampak Penggunaan Atribut Keagamaan terhadap Pola Persepsi Konsumen Muslim di Pasar Banyuasri, Buleleng - Muhammad Idris; Mahir Pradana (Universitas Muhammadiyah Makassar, 2023)
This article aims to understand the influence of religious attributes on the perception patterns of Muslim consumers as a basic basis for determining intentions to make choices based on religious symbols in the Banyuasri market, Buleleng, Bali. This study uses a phenomenological study method with a qualitative approach with descriptive data analysis. The results of the study show that religious attributes have a significant impact on the perception patterns of Muslim consumers in the Banyuasri market. Muslim consumers have a tendency to make choices based on consideration of strong religious symbols, such as headscarves, caps, and the use of daily symbols in the form of canang for Balinese Hindus. The strength of symbolic capital, especially in the use of religious attributes, can be an important factor in understanding the preferences and decisions of Muslim consumers in trading activities. Muslim consumers in Singaraja have a tendency to consider everything based on the main religious aspect in determining the choice of products and services they will buy.